ANTIBACTERIAL ACTIVITY OF AQUEOUS GARLIC EXTRACT ON BETA-LACTAMASE PRODUCING ACINETOBACTER ISOLATES FROM SKIN AND SOFT TISSUE INFECTIONS - Shah, Pratibha J; MANITA T WILLIAMSON,; SEJAL J RATHOD, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study evaluates the antibacterial effect of aqueous garlic extract (AGE) on beta-lactamase producing Acinetobacter strains isolated from skin and soft tissue infections (SSTIs). Methods: A total of 41 non-duplicate strains of Acinetobacter isolated from SSTIs specimens were tested for their antibiotic susceptibility pattern by Kirby-Bauer disk diffusion method. Ceftazidime-resistant Acinetobacter strains were screened for beta-lactamase production by Phenotypic confirmatory disc diffusion test (PCDDT) and E-test. Antibacterial activity of AGE was examined by the disc diffusion method and the minimum inhibitory concentration (MIC) of AGE and Cefotaxime was determined by the agar dilution technique. The combined activity of AGE and Cefotaxime was evaluated by calculating the fractional inhibitory concentration (FIC) index by the checkerboard method. Results: 21 Acinetobacter strains were confirmed to be beta-lactamase producers, out of which 6 were Metallo-beta-lactamase (MBL) producers, 3 were Ambler Class C (AmpC) and 12 were multiple beta-lactamase producers. AGE exhibited significant antibacterial activity as the observed zones of inhibition ranged from 18 - 31 mm against the test strains. The MIC of AGE was in the range of 0.5% - 2% (2.5 mg/ml – 10 mg/ml) with a mean of 0.86% (4.28 mg/ml). 11 test strains showed synergism, 5 strains exhibited additive and indifferent effect, each. By HPLC analysis the concentration of allicin was found to be 0.20, expressed as percentage w/w. Conclusion: It can be stated that aqueous garlic extract might have therapeutic value against beta-lactamase producing Acinetobacter isolates from SSTIs.